2022
DOI: 10.3390/agronomy12061479
|View full text |Cite
|
Sign up to set email alerts
|

Boron Effects on Fruit Set, Yield, Quality and Paternity of Hass Avocado

Abstract: Boron plays a critical role in pollination and fertilization and can affect fruit set and yield. We applied 0 g, 15 g (manufacturer recommendation) or 30 g boron pre-flowering to Hass avocado trees to determine the effects on fruit set, fruitlet paternity, yield, fruit size, mineral nutrient concentrations and fatty acid composition. The boron applications did not significantly affect the initial fruit set at 3 or 6 weeks after peak anthesis or the proportions of self-pollinated fruitlets or mature fruit. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…At a higher B rate (3 kg ha −1 ), the values of all the gas exchange parameters declined, suggesting that this amount of B fertilizer was unnecessary under the studied conditions. Moreover, it is widely established that excessive B application may hinder photosynthesis [24][25][26] and reduce yield [27,28]. During the study period, especially in the first and second years, B application at the highest rate (3 kg ha −1 ) resulted in the lowest yield, but the difference relative to other B rates was not statistically significant.…”
Section: Discussionmentioning
confidence: 88%
“…At a higher B rate (3 kg ha −1 ), the values of all the gas exchange parameters declined, suggesting that this amount of B fertilizer was unnecessary under the studied conditions. Moreover, it is widely established that excessive B application may hinder photosynthesis [24][25][26] and reduce yield [27,28]. During the study period, especially in the first and second years, B application at the highest rate (3 kg ha −1 ) resulted in the lowest yield, but the difference relative to other B rates was not statistically significant.…”
Section: Discussionmentioning
confidence: 88%
“…Nutrient toxicities in avocado can also occur due to the excessive use of fertiliser. For example, B is a critical nutrient for avocado fruit set and yield, but high B concentrations can cause fruitlet abscission and reduce yield [36]. Rapid nutrient assessment tools such as hyperspectral imaging could help growers detect nutrient deficiencies or toxicities in crops in real time, reduce fertiliser costs and manage nutrient applications more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves were collected from 30 Hass trees located at the Eastridge avocado orchard (25 • 13 25 S 152 • 18 54 E), near Childers, Queensland, Australia. These trees were used in a previous complementary study on the effect of boron applications on avocado fruit set, yield and quality [36]. Four heterogeneous leaves were randomly collected from each experimental tree on each of four occasions: 0, 6, 10 and 28 weeks after peak flower anthesis.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, these reproductive buds develop into complex, multi-branched panicles where the flowers emerge. According to [53], it has been observed that a single tree can bear an impressive number of panicles, with the potential to produce up to a million flowers. The panicles typically exhibit a determinate nature, devoid of any leafy buds emerging from them.…”
Section: Phenologymentioning
confidence: 99%